2020
DOI: 10.1080/17476348.2020.1746647
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome of pleurodesis in patients with malignant pleural effusion: a systematic review and meta-analysis

Abstract: Objectives: Pleurodesis is an important management option to palliate breathlessness in patients with malignant pleural effusion (MPE). This systematic review aimed to examine available literature for studies investigating factors that predict pleurodesis outcome.Methods: the healthcare databases advanced search (HDAS) Medline and Embase in addition to Cochrane Database of Systematic Reviews were searched on for publications reporting on pleurodesis for MPE in English language. All studies types reporting prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…CRD42018115874). The primary outcome of the review along with the full search strategy and risk of bias assessment are reported elsewhere [ 5 ]. The literature search was carried out on Medline, Embase and Cochrane Database of Clinical trials on 12th November 2018 and updated for the purpose of this review on 1st July 2020.…”
Section: Methodsmentioning
confidence: 99%
“…CRD42018115874). The primary outcome of the review along with the full search strategy and risk of bias assessment are reported elsewhere [ 5 ]. The literature search was carried out on Medline, Embase and Cochrane Database of Clinical trials on 12th November 2018 and updated for the purpose of this review on 1st July 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the IPC group had larger effusions, and more were receiving systemic steroid therapy at the time of trial recruitment; which may have had an effect. [13,14] The IPC-PLUS trial, which primarily examined pleurodesis outcomes via an IPC, reported a 43% pleurodesis success rate at 35 days post-talc insufflation, [2] which is slightly higher than the rate of pleurodesis success at Day 30 (35%) in this study. However, differences in drainage protocols (affecting the degree of pleural apposition) and patient selection may account for this disparity.…”
Section: Discussionmentioning
confidence: 54%
“…However, there have been contradictory results. A metaanalysis of 42 studies demonstrated that the strongest predictors of pleurodesis success were higher pleural fluid pH, smaller volume of effusion before pleurodesis and full lung re-expansion after effusion drainage (34). Higher pleural fluid glucose, lower LDH, lower pleural tumour burden, and shorter duration of tube drainage seem to favour pleurodesis success.…”
Section: Discussionmentioning
confidence: 99%
“…Higher pleural fluid glucose, lower LDH, lower pleural tumour burden, and shorter duration of tube drainage seem to favour pleurodesis success. However, data from these studies were limited by statistical heterogeneity (34). It is not known how well serum biomarkers correlate with pleural inflammation.…”
Section: Discussionmentioning
confidence: 99%